2019
DOI: 10.1152/ajpregu.00345.2018
|View full text |Cite
|
Sign up to set email alerts
|

α-Adrenergic receptor regulation of skeletal muscle blood flow during exercise in heart failure patients with reduced ejection fraction

Abstract: Patients suffering from heart failure with reduced ejection fraction (HFrEF) experience impaired limb blood flow during exercise, which may be due to a disease-related increase in α-adrenergic receptor vasoconstriction. Thus, in eight patients with HFrEF (63 ± 4 yr) and eight well-matched controls (63 ± 2 yr), we examined changes in leg blood flow (Doppler ultrasound) during intra-arterial infusion of phenylephrine (PE; an α1-adrenergic receptor agonist) and phentolamine (Phen; a nonspecific α-adrenergic recep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 61 publications
1
20
0
Order By: Relevance
“…COVID-19 is associated with increased sympathetic activity which results in peripheral vasoconstriction. We, and others, have consistently reported that age-and disease-related increases in sympathetic activity are associated with diminished blood flow, especially at lower exercise intensities (44)(45)(46). As exercise intensity increases, local factors overcome this sympathetically-mediated vasoconstriction, a process termed functional sympatholysis (47), potentially resulting in preserved blood flow at higher exercise intensities, even with COVID-19.…”
Section: Vascular Function and Blood Flowmentioning
confidence: 93%
“…COVID-19 is associated with increased sympathetic activity which results in peripheral vasoconstriction. We, and others, have consistently reported that age-and disease-related increases in sympathetic activity are associated with diminished blood flow, especially at lower exercise intensities (44)(45)(46). As exercise intensity increases, local factors overcome this sympathetically-mediated vasoconstriction, a process termed functional sympatholysis (47), potentially resulting in preserved blood flow at higher exercise intensities, even with COVID-19.…”
Section: Vascular Function and Blood Flowmentioning
confidence: 93%
“…Furthermore, a subsequent study showed that muscle SNA was significantly higher while peak oxygen uptake was significantly lower in patients with ischemic vs nonischemic cardiomyopathy[ 171 ]. The most recent clinical study also demonstrated that the α-adrenergic-mediated vasoconstriction in HFrEF patients elicited a marked decrease in exercising skeletal muscle blood flow thus contributing to reduced exercise capacity in this population[ 172 ]. Finally, HF patients present with a high degree of chronotropic incompetence and attenuated heart rate response to exercise which is partially due to postsynaptic desensitization of the β-adrenergic receptor pathways[ 173 ].…”
Section: Sympathetic Nervous System Pathophysiology and Adrenergic Dymentioning
confidence: 99%
“…Multiple studies have shown an increase in vascular responsiveness to α 1 -AR stimulation in animals [114][115][116][117]119,120,122,[129][130][131]. On the contrary, others have reported desensitization of α 1 -ARs in the peripheral vasculature in animals [102,121,[132][133][134][135][136] and in humans [137][138][139][140], while numerous studies failed to demonstrate any alterations of the α 1 -AR responsiveness in vessels from animals [105,123,133,[141][142][143] and humans [144]. Inconsistency in findings might originate from differences in the anatomy and function of distinct vascular beds.…”
Section: Cell and Tissuementioning
confidence: 99%